Fruit and vegetable intake in the Mexican population: results from the Mexican National Health and Nutrition Survey 2006 Consumo de frutas y verduras en la población mexicana - Ivonne Ramírez-Silva; Juan A Rivera; Xochitl Ponce; Mauricio Hernández-Ávila (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To quantify fruit and vegetable (FV) dietary intake in the Mexican population and compliance with international recommendations. MATERIAL AND METHODS: FV dietary intake (FV-DI) and compliance with international recommendations were obtained in a representative sample of a Mexican population ages 1-59 years old using dietary data from the Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006). RESULTS: Average FV-DI for different age groups range from 61 to 72 g for fruits and 26 to 56 g for vegetables. Average total FV intakes were 88.7 g in preschool-age, 103.1 g in school-aged children, 116.3 g in adolescents and 122.6 g in adults. The lowest intakes were observed in the northern region and among the population with the lowest wellbeing levels. CONCLUSIONS: Less than 30% of the Mexican population had adequate intakes of FV. Developing and implementing strategies aimed at increasing intake of these food groups is a national priority. OBJETIVO: Cuantificar la ingestión dietética de frutas y verduras y el apego a recomendaciones internacionales en la población mexicana. MATERIAL Y MÉTODOS: La ingestión dietética de frutas y verduras y el apego a recomendaciones fueron obtenidas en una muestra representativa de la población mexicana de entre 1 a 59 años de edad, usando datos sobre dieta de la Encuesta Nacional de Salud y Nutrición 2006 (ENSANUT 2006). RESULTADOS: Los promedios de ingestión dietética para los diversos grupos de edad fluctuaron entre 61 y 72 g en frutas y 26 y 56 g en verduras. Los promedios de ingestión dietética total de frutas y verduras fueron: 87.5 g en preescolares, 103.1 g en escolares, 116.3 g en adolescentes y 122.6 g en adultos. Los menores consumos se observaron en la región norte y en la población con los menores niveles de bienestar. CONCLUSIONES: Menos de 30% de la población tuvo consumos adecuados. El desarrollo e implementación de estrategias y programas que contribuyan a aumentar el consumo de estos alimentos es de alta prioridad.